The Use Of Job Interview Simulation In Enhancing English Speaking Skills At Ninth Grade Students Of MTs NWDI Pringgasela - Peri Adrian; M. Adib Nazri; Muhammad Husnu; Zahratul Fikni (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
The aim of this research is to enhance students' English speaking skills through interview simulation techniques with job application material, making them more active. This research uses experimental techniques that combined with quantitative research techniques through direct speaking tests. The research questions considered in this study are: What are interview simulation techniques effective in enhancing students' English speaking skills? How can interview simulation techniques enhance students' English speaking skills? The aim of this research is to determine the effectiveness of interview simulation techniques in improving students' English language skills. To assess student results regarding the use of interview simulation techniques in teaching speaking to enhance abilities. This research method consists of pre-test, treatment, post-test. The analytical methods used for data processing are included in Social Science Statistics 22.0 for Windows. The result was that before applying the interview simulation technique, only 50% of students were able to speak English. After applying the interview simulation technique, it increased students' ability to speak English by 80%. Analysis of student test results shows that the interview simulation technique is effective in enhancing students' English speaking skills. Applying simulation techniques in learning English, especially speaking, is the right strategy to enhance students' skills.